Composite photocatalyst material as well as preparation method and application thereof
Through the composite photocatalyst material of Ni-BDC MOF and γ-MnO2, the problem of poor visible light absorption capacity and high electron-hole recombination rate of photocatalysts in CO2 reduction is solved, and efficient CO2 reduction under conventional environmental conditions is achieved, reducing Energy consumption and the risk of using toxic solvents are significantly improved catalytic efficiency and economicality.
Patent Information
- Application Number
- CN202411631257.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
In CO2 reduction, existing photocatalysts have problems such as poor visible light absorption capacity, high recombination rate of electron-hole pairs, high energy operating conditions and the use of toxic and harmful solvents.
Using Ni-BDC MOF and γ-MnO2 composite photocatalyst material, the band gap is reduced by incorporating γ-MnO2 into Ni-BDC MOF, thereby enhancing the visible light absorption capacity and charge separation capacity, and reducing the re-binding of electrons and holes. And efficient reduction of CO2 under conventional environmental conditions to avoid the use of harmful solvents.
It significantly improves the visible light absorption capacity and CO2 reduction efficiency of the photocatalyst, and can effectively catalyze CO2 reduction to CO and CH4 at room temperature and pressure, reducing energy consumption and operating costs, and achieving environmentally friendly and efficient catalysis.
Smart Images

Figure CN119281399A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalysis, and in particular to a Ni-BDC MOF / γ-MnO2 composite photocatalyst material, a preparation method and application thereof in high-efficiency catalytic reduction of carbon dioxide (CO2). Technical Background
[0002] With the intensification of global warming and climate change, the reduction and conversion of greenhouse gases (especially CO2) has become a research hotspot. Among them, photocatalytic reduction of CO2 is a very promising solution that can not only reduce CO2 emissions, but also produce high-value fuels such as CO and CH4.
[0003] There are three main types of photocatalysts currently used for CO2 reduction:
[0004] (1) Metal-organic framework compounds (MOFs materials): Due to their porous structure, high specific surface area, and adjustable properties, MOFs materials have shown great application prospects in photocatalysis. MOFs materials are composed of metal ions or clusters connected by organic ligands to form a three-dimensional network structure. They can achieve specific functions or chemical reactions through structural design and have attracted much attention in the field of CO2 reduction.
[0005] (2) Semiconductor photocatalysts: Due to their strong light absorption ability and stable generation of electron-holes, semiconductor photocatalysts (such as TiO2, ZnO, etc.) are widely used in the field of CO2 reduction.
[0006] (3) MOFs-semiconductor composite photocatalysts: By combining MOFs materials with semiconductors to achieve synergistic effects, the light absorption capacity, electron-hole separation ability and overall photocatalytic performance are improved. For example, composite photocatalyst materials such as MOFs-TiO2 and MOFs-g-C3N4.
[0007] The existing photocatalyst systems have the following main disadvantages:
[0008] (1) Poor visible light absorption: Traditional MOFs photocatalysts and many semiconductor photocatalysts have difficulty absorbing visible light effectively due to their high band gaps. This limits their photocatalytic efficiency in CO2 reduction applications using sunlight as an energy source.
[0009] (2) High recombination rate of electron-hole pairs: After absorbing light source, photocatalysts will generate electron-hole pairs to drive the reduction reaction of CO2. However, in many current photocatalyst systems, electron-hole pairs are prone to recombine before being effectively used in the catalytic reaction, significantly reducing the photocatalytic efficiency.
[0010] (3) Requirement of high-energy operating conditions: Some photocatalysts require high temperature or high pressure operating conditions to achieve significant CO2 reduction rates, which will increase energy consumption and operating costs.
[0011] (4) Use of toxic and harmful reagents: Currently, most photocatalyst systems require the use of toxic and harmful organic solvents, which are not only harmful to the environment but also make the photocatalytic reaction process more complicated. Summary of the invention
[0012] The present invention aims to solve the technical problems of the current photocatalysts used for CO2 reduction, such as poor visible light absorption, high recombination rate of electron-hole pairs, high energy operating conditions and the use of toxic and hazardous solvents.
[0013] In view of this, the present invention provides a Ni-BDC MOF / γ-MnO2 composite photocatalyst material, a preparation method and its application in the efficient catalytic reduction of carbon dioxide (CO2). By doping γ-MnO2 into the Ni-BDC MOF material, the band gap is reduced from 3.16eV to about 2.7eV, a wider visible light absorption capacity is achieved, the charge separation ability is enhanced, and the electron-hole recombination rate is reduced. The Ni-BDC MOF / γ-MnO2 composite photocatalyst material provided by the present invention can not only effectively catalyze the reaction of CO2 reduction to CO and CH4 under visible light and conventional environmental conditions, but also does not require the use of harmful solvents, taking into account both economic benefits and environmental friendliness.
[0014] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0015] A Ni-BDC MOF / γ-MnO2 composite photocatalyst material, wherein the Ni-BDCMOF has a two-dimensional sheet structure and Ni that adsorbs CO2 2+ Active sites provide a framework for CO2 adsorption and reduction. The γ-MnO2 is added to the Ni-BDC MOF to form a heterojunction. The γ-MnO2 component improves light absorption and enhances charge separation.
[0016] Furthermore, MnO2 particles are distributed on the surface of Ni-BDC MOF to form a continuous heterojunction interface.
[0017] Furthermore, MnO2 was doped into Ni-BDC MOF.
[0018] Further, including any heterojunction structure formed between the Ni-BDC MOF and γ-MnO2, the composite photocatalyst material can enhance the photocatalytic CO2 reduction activity, including in the visible light spectrum.
[0019] The present invention also provides an application of the Ni-BDCMOF / γ-MnO2 composite photocatalyst material according to claim 1, wherein the Ni-BDCMOF / γ-MnO2 composite photocatalyst material is used to photocatalytically reduce CO2 to CO and CH4 under visible light irradiation.
[0020] Furthermore, CO2 is first adsorbed on the Ni 2+ The active site is then subjected to electron transfer-induced reduction, ultimately forming CO or CH4 products.
[0021] Furthermore, the Ni-BDCMOF / γ-MnO2 composite photocatalyst material is used in any photocatalytic system to reduce CO2 emissions by converting CO2 into CO and CH4.
[0022] The present invention also provides a method for preparing a Ni-BDC MOF / γ-MnO2 composite photocatalyst material, comprising the following steps:
[0023] (1) Disperse γ-MnO2 in DMF by ultrasonic method, which is labeled as solution A;
[0024] (2) Terephthalic acid was dispersed in DMF, labeled as solution B;
[0025] (3) Ni(NO3)2·6H2O dissolved in deionized water, labeled as solution C;
[0026] (4) While stirring, add solution A to solution B, and then add solution C dropwise to the mixed solution of solutions A and B, and continue stirring after the addition is completed;
[0027] (5) The obtained mixed solution is transferred to a hydrothermal reactor and heated for a certain period of time;
[0028] (6) Filter the precipitate, dry it, and obtain the Ni-BDC MOF / γ-MnO2 composite photocatalyst material.
[0029] Preferably, the amount of Ni(NO3)2·6H2O in step (3) is 7.5 mmol.
[0030] Preferably, the mixed solution obtained in step (5) is transferred to a hydrothermal reactor and heated at 180° C. for 24 h.
[0031] The structural characteristics of the Ni-BDC MOF / γ-MnO2 composite photocatalyst material of the present invention are as follows:
[0032] Ni-BDC MOF material - a two-dimensional sheet structure with high specific surface area and abundant CO2 adsorption active sites.
[0033] γ-MnO2 material - a transition metal oxide with a low band gap and excellent electron transfer ability.
[0034] Ni-BDC MOF / γ-MnO2 composite photocatalyst material - Ni-BDC MOF forms a heterojunction with γ-MnO2 to improve the reaction activity of photocatalytic CO2 reduction through better carrier dynamics and wider visible light absorption range.
[0035] Compared with the prior art, the present invention has the following technical advantages:
[0036] (1) Enhance the absorption capacity of visible light
[0037] Prior art: Conventional photocatalysts such as TiO2 and ZnO typically have large band gaps (3.0-3.2 eV), limiting their ability to absorb visible light, restricting them to UV-driven photocatalysis.
[0038] The present invention: Ni-BDC MOF / γ-MnO2 composite material reduces the overall band gap to 2.7eV and significantly enhances light absorption in the visible spectrum (400-700nm). This allows the material to function more effectively under natural sunlight, increasing its practicality in large-scale reduction of CO2.
[0039] (2) Promote charge separation and inhibit electron-hole recombination
[0040] State of the art: MOF-based photocatalysts often suffer from rapid electron-hole recombination, limiting the number of charge carriers available for CO2 reduction and reducing the overall efficiency.
[0041] The present invention: γ-MnO2 is combined with Ni-BDC MOF to form a heterojunction, which promotes effective charge separation. The electrons generated in the conduction band of γ-MnO2 are transferred to the conduction band of Ni-BDC MOF, while the holes remain in the valence band of γ-MnO2. This effectively inhibits the recombination of electrons and holes, increases the lifetime of carriers, and thus improves the photocatalytic efficiency.
[0042] (3) Increase the types of CO2 reduction products
[0043] Existing technology: Many photocatalysts mainly produce CO through CO2 reduction, while the production of other valuable chemicals (such as CH4) is limited.
[0044] The present invention: Ni-BDC MOF / γ-MnO2 composite material can not only achieve high CO production, but also form CH4. This dual performance makes the present invention more versatile and economically advantageous, because both CO and CH4 are valuable chemical fuels.
[0045] (4) Stable photocatalytic performance under normal environmental conditions
[0046] Existing technologies: Many existing photocatalytic systems require high temperatures, high pressures or the use of organic solvents, which increases the complexity and cost of the photocatalytic process.
[0047] The present invention: The composite material can work effectively at normal temperature and pressure, without the need for organic solvents or sacrificial agents. This makes the process more environmentally friendly and cost-effective in industrial applications.
[0048] (5) Realizing the synergistic effect of MOF and semiconductor
[0049] Existing technology: In previous MOF and semiconductor composites, the synergy between the two materials is often weak, resulting in limited performance improvements.
[0050] The present invention: The combination of Ni-BDC MOF and γ-MnO2 exhibits a strong synergistic effect, wherein the MnO2 particles enhance the electronic properties of MOF while maintaining the high specific surface area and selective CO2 adsorption capacity of Ni-BDCMOF.
[0051] (6) Scalability and practicality
[0052] Existing Technology: Many existing technology systems are not easily scalable because they rely on expensive catalyst materials such as platinum or gold catalysts.
[0053] The present invention: The use of relatively cheap materials, such as Ni-BDC MOF and MnO2, makes this composite material more cost-effective and scalable for industrial applications. The ability to operate under normal temperature and pressure conditions further enhances its scalability in CO2 reduction applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 XRD spectra of Ni-BDC MOF, γ-MnO2 and their composites;
[0055] Figure 2 This is the SEM image of Ni-BDC MOF / γ-MnO2 composite photocatalyst material;
[0056] Figure 3 This is the UV-visible spectrum test result of Ni-BDC MOF / γ-MnO2 composite photocatalyst material;
[0057] Figure 4 Kubelka-Munk plot of Ni-BDC MOF / γ-MnO2 composite photocatalyst material;
[0058] Figure 5This is the DRIFT absorption spectrum of Ni-BDC MOF / γ-MnO2 composite photocatalyst material;
[0059] Figure 6 It is a schematic diagram of the energy band. DETAILED DESCRIPTION
[0060] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. On the contrary, the present invention encompasses any substitutions, modifications, equivalent methods and schemes made on the essence and scope of the present invention as defined by the claims. Further, in order to enable the public to have a better understanding of the present invention, some specific details are described in detail in the detailed description of the present invention below. For those skilled in the art, the present invention can be fully understood without the description of these details.
[0061] In an embodiment of the present invention, a method for preparing a Ni-BDC MOF / γ-MnO2 composite photocatalyst material comprises the following steps:
[0062] (1) Disperse γ-MnO2 in DMF by ultrasonic method, which is labeled as solution A;
[0063] (2) Terephthalic acid was dispersed in DMF, labeled as solution B;
[0064] (3) Ni(NO3)2·6H2O dissolved in deionized water, labeled as solution C;
[0065] (4) While stirring, add solution A to solution B, and then add solution C dropwise to the mixed solution of solutions A and B, and continue stirring after the addition is completed;
[0066] (5) The obtained mixed solution is transferred to a hydrothermal reactor and heated for a certain period of time;
[0067] (6) Filter the precipitate, dry it, and obtain the Ni-BDC MOF / γ-MnO2 composite photocatalyst material.
[0068] The Ni-BDC MOF / γ-MnO2 composite photocatalyst material of the present invention can be used to efficiently catalyze the reduction of carbon dioxide (CO2) under visible light.
[0069] In the present invention:
[0070] 1. Material composition
[0071] The present invention comprises a novel Ni-BDC MOF / γ-MnO2 composite material, comprising:
[0072] (1) Ni-BDC MOF (Ni-1,4-dimethyl phthalate metal-organic framework), with a two-dimensional sheet structure and Ni for CO2 adsorption 2+ Active site.
[0073] (2) γ-MnO2, added to Ni-BDC MOF to form a heterojunction, improves the photocatalytic performance of the composite material.
[0074] in:
[0075] Ni-BDC MOF provides a framework for CO2 adsorption and reduction.
[0076] The γ-MnO2 component improves light absorption and enhances charge separation.
[0077] The present invention extends to any heterojunction structure formed between Ni-BDC MOF and γ-MnO2, thereby enhancing the photocatalytic CO2 reduction activity, especially in the visible light spectrum.
[0078] 2.CO2 reduction process
[0079] The unique photocatalytic process achieved by the composite material of the present invention includes:
[0080] (1) Due to the lowered bandgap provided by the introduction of γ-MnO2, a wider range of visible light absorption is achieved.
[0081] (2) The charge separation and transfer process between γ-MnO2 and Ni-BDC MOF improves the photocatalytic efficiency of CO2 reduction.
[0082] The invention discloses a method for photocatalytically reducing CO2 to CO and CH4 using a Ni-BDC MOF / γ-MnO2 composite material under visible light irradiation.
[0083] The present invention covers the CO2 reduction reaction pathway, in which CO2 is first adsorbed on the Ni of Ni-BDCMOF. 2+ The active site is then subjected to electron transfer-induced reduction, ultimately forming CO or CH4 products.
[0084] 3. Structural design
[0085] The specific structural arrangement and combination between Ni-BDC MOF and MnO2 of the present invention includes:
[0086] (1) Physical distribution of MnO2 in Ni-BDC MOF material.
[0087] (2) The formation of a heterojunction that can enhance charge transfer properties.
[0088] The physical structure of the Ni-BDC MOF / γ-MnO2 composite material is protected, in which MnO2 particles are distributed on the surface of Ni-BDC MOF to form a continuous heterojunction interface.
[0089] 4. Improvement of photocatalytic efficiency
[0090] The improvement of the photocatalytic efficiency of the present invention is due to the following two points:
[0091] (1) The band gap of the composite material is reduced from 3.16 eV to 2.7 eV, promoting a wider range of visible light absorption;
[0092] (2) The γ-MnO2 component promotes the separation of electrons and holes and prevents their rapid recombination.
[0093] The present invention adds MnO2 into Ni-BDC MOF, reduces the band gap of the composite material, and enhances the ability of the material to absorb visible light.
[0094] The invention discloses a method for enhancing charge separation capability and inhibiting rapid electron-hole recombination in a composite material, thereby improving the overall efficiency of a CO2 reduction process.
[0095] 5. Application of photocatalytic system
[0096] The composite material of the present invention is used in a photocatalytic system for:
[0097] (1) Reduce CO2 emissions by converting CO2 into valuable chemicals (CO and CH4).
[0098] (2) Produce chemical fuels through sustainable photocatalytic processes for green energy production.
[0099] The present invention extends to the use of Ni-BDC MOF / γ-MnO composites in various photocatalytic systems aimed at reducing CO2 emissions and producing valuable fuels such as CO and CH4.
[0100] The reaction principle of photocatalytic CO2 reduction of the Ni-BDC MOF / γ-MnO2 composite photocatalyst material of the present invention is as follows:
[0101] The working principle of the present invention is to use Ni-BDC MOF / γ-MnO2 composite material to carry out photocatalytic CO2 reduction reaction. The large specific surface area of Ni-BDC MOF allows the adsorption of CO2, and MnO2 ensures the extensive absorption of visible light. The electron transfer kinetics between Ni-BDC MOF and MnO2 hinders the rapid recombination of electrons and holes. The specific reaction principle is as follows:
[0102] (1) Visible light absorption and charge generation: As the band gap decreases from 3.16 eV to 2.7 eV, the composite material can effectively absorb visible light and excite electrons from the valence band to the conduction band.
[0103] (2) Charge separation and transfer: The heterojunction between Ni-BDC MOF and MnO2 plays a key role in charge separation. Once light energy is absorbed, electron-hole pairs are generated in Ni-BDC MOF, and then γ-MnO2 achieves effective charge separation by transferring electrons from the conduction band of γ-MnO2 to the conduction band of Ni-BDC MOF, leaving holes in the valence band of γ-MnO2. This prevents the rapid recombination of electrons and holes, which helps to improve the overall photocatalytic efficiency.
[0104] (3) CO2 adsorption and activation: CO2 molecules are adsorbed on the active sites of Ni-BDC MOF (mainly Ni 2+ center), interacting with the electron-rich region, weakening the CO bond of CO2 and preparing for the reduction of CO2.
[0105] (4) CO2 is reduced to CO and CH4: The electrons separated from the conduction band of the composite photocatalyst material combine with the CO2 molecules on the surface of Ni-BDC MOF to form reaction intermediate species (such as *CO2 - ), the hole left in the valence band of γ-MnO2 oxidizes the H2O molecule. Promoted by the oxidation of water molecules, the intermediate species will be further converted into CO or CH4 depending on the reaction conditions and the number of transferred electrons.
[0106] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.
[0107] Example 1
[0108] A method for preparing a Ni-BDC MOF / γ-MnO2 composite photocatalyst material comprises the following steps:
[0109] (1) γ-MnO2 was ultrasonically dispersed in 10 ml of DMF, labeled as solution A;
[0110] (2) 7.5 mmol of terephthalic acid was dispersed in 15 ml of DMF, labeled as solution B;
[0111] (3) 7.5 mmol of Ni(NO3)2·6H2O was dissolved in 15 ml of deionized water, labeled as solution C;
[0112] (4) While stirring, add solution A to solution B, and then add solution C dropwise to the mixed solution of solutions A and B. Continue stirring for 30 min after the addition is completed;
[0113] (5) The obtained mixed solution was transferred to a hydrothermal reactor and heated at 180°C for 24 h;
[0114] (6) The precipitate was filtered and dried for 24 hours to obtain a Ni-BDC MOF / γ-MnO2 composite photocatalyst material.
[0115] Figure 1 The characteristic diffraction peaks of Ni-BDC MOF and γ-MnO2 prepared in Example 1 of the present invention are shown. The composite material retains the characteristic peaks of Ni-BDC MOF and also has new peaks corresponding to γ-MnO2, which confirms the successful formation of the composite material.
[0116] Figure 2 The SEM images show that Ni-BDC MOF is a large-sized flake structure, and small-sized γ-MnO2 particles are dispersed on the surface of Ni-BDC MOF. The composite material retains the morphological characteristics of Ni-BDC MOF and γ-MnO2.
[0117] Figure 3 It shows that the light absorption of the Ni-BDC MOF / γ-MnO2 composite material prepared in Example 1 of the present invention is enhanced in the visible light region.
[0118] Figure 4 It was further confirmed that the reduction of the band gap of the composite material enhanced the photocatalytic activity.
[0119] Figure 5 The formation of intermediate species formed in the photocatalytic reaction was confirmed.
[0120] Figure 6 The transfer of electrons and holes in the reduction reaction in the photocatalyst is shown.
[0121] The following further details possible alternatives to the Ni-BDC MOF / γ-MnO2 composite system, including replacement or modification of the structure, material structure or process steps. These alternatives can expand the scope of the invention protection and ensure that the changes in the method still fall within the scope of the invention protection.
[0122] 1. Material Alternatives
[0123] (1) Alternative MOF materials
[0124] The present invention mainly uses Ni-BDC MOF (nickel-based), but other MOFs with similar properties can also be substituted to achieve similar results for photocatalytic CO2 reduction. These alternative MOF materials can provide different metal active centers to improve the selectivity or reactivity of CO2 reduction. These alternatives include:
[0125] Cu-BDC MOF (copper-based MOF): Like Ni-BDC, Cu-BDC has high specific surface area and CO2 adsorption capacity. The copper center can replace nickel to interact with CO2 while maintaining a large specific surface area and photocatalytic activity.
[0126] Zirconium-based MOFs (such as UiO-66): Zirconium-based MOFs have structural stability and can accommodate various functional groups. Zirconium-based MOFs can be modified to introduce active metal centers to promote the reduction of CO2.
[0127] (2) Alternative semiconductor materials
[0128] In addition to γ-MnO2, other semiconductor materials with suitable electronic properties can also be used to form heterojunctions with Ni-BDC MOF, such as:
[0129] Titanium dioxide (TiO2): TiO2 is a widely studied photocatalyst with a strong ability to generate electron-hole pairs under UV and visible light. Modified TiO2 or doped TiO2 can be combined with Ni-BDC MOF to achieve similar photocatalytic CO2 reduction performance.
[0130] Zinc oxide (ZnO): Zinc oxide is another semiconductor with a low band gap and good electron mobility. It can replace γ-MnO2 to form a heterojunction with MOF, promoting charge separation and visible light absorption.
[0131] Graphitized carbon nitride (g-C3N4): This material has been used in photocatalytic applications for CO2 reduction due to its narrow band gap and visible light activity. It can be used as an alternative co-catalyst for Ni-BDC MOF composites to achieve similar catalytic performance improvements.
[0132] 2. Alternatives to composite structures
[0133] (1) Alternative heterojunction structures
[0134] The heterojunction between Ni-BDC MOF and γ-MnO2 is the key to improving charge separation and suppressing electron-hole recombination. In addition to dispersing MnO2 particles on the surface of Ni-BDC MOF to form a heterojunction structure, alternative solutions to achieve the heterojunction structure may include:
[0135] Layer-by-layer assembly: Alternating the Ni-BDC MOF layers and the MnO2 layers into a layered structure can achieve a closer contact between the two phases and enhance the charge transfer capability.
[0136] Core-shell structure: MnO2 can form a core and Ni-BDC MOF can form a shell around it, or vice versa. This arrangement ensures charge transfer across the interface, reducing recombination while enhancing light absorption.
[0137] (2) Alternative carrier materials
[0138] In addition to using Ni-BDC MOF as a carrier, other carrier materials can also be selected to fix or support MOF or semiconductor composite materials. For example:
[0139] Graphene or carbon nanotubes (CNTs): Graphene sheets or carbon nanotubes can act as supporting structures, provide high conductivity and improve electron transfer in composite materials. The combination of graphene-based materials with MOF or MnO2 can provide better charge separation and photocatalytic performance.
[0140] 3. Alternatives to photocatalytic processes
[0141] (1) Alternative light sources
[0142] While this invention focuses on visible light as the primary energy source, other light sources can also be used to drive the photocatalytic process, providing flexibility in practical applications. These include:
[0143] UV light: UV light irradiation can be used with modified or doped Ni-BDC MOF or γ-MnO2 to enhance the photocatalytic activity for CO2 reduction.
[0144] Near-infrared light: Certain doped semiconductors and MOF materials are able to absorb near-infrared light. By adjusting the band gap through doping, the material can respond to near-infrared light, thereby activating the photocatalyst of the present invention.
[0145] (2) Alternative solvents
[0146] The photocatalytic reaction of the present invention is operated under aqueous conditions, making it more environmentally friendly. However, in some cases, alternative solvents or solvent systems may improve catalytic performance or product selectivity:
[0147] Ionic liquids: Ionic liquids are excellent solvents for capturing carbon dioxide. Using ionic liquids as solvents for the CO2 reduction process can improve the adsorption efficiency and increase the conversion rate of CO2 to CO or CH4.
[0148] Organic solvents: In some cases, specific organic solvents may increase the rate of the photocatalytic reaction. Although the present invention is designed to work without organic solvents, the introduction of small amounts of specific organic solvents can increase the selectivity of the product.
Claims
1. A Ni-BDC MOF / γ-MnO2 composite photocatalyst material, characterized in that: The Ni-BDC MOF has a two-dimensional sheet structure and Ni for adsorbing CO2. 2+ Active sites provide a framework for CO2 adsorption and reduction. The γ-MnO2 is added to the Ni-BDC MOF to form a heterojunction. The γ-MnO2 component improves light absorption and enhances charge separation.
2. The Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 1, characterized in that: MnO2 particles are distributed on the surface of Ni-BDC MOF to form a continuous heterojunction interface.
3. The Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 1, characterized in that: MnO2 was doped into Ni-BDC MOF.
4. The Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 1, characterized in that: Including any heterojunction structure formed between the Ni-BDC MOF and γ-MnO2, the composite photocatalyst material can enhance the photocatalytic CO2 reduction activity, including in the visible light spectrum.
5. An application of the Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 1, characterized in that: The Ni-BDC MOF / γ-MnO2 composite photocatalyst material is used to photocatalytically reduce CO2 to CO and CH4 under visible light irradiation.
6. The use of the Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 5, characterized in that: CO2 is first adsorbed on the Ni 2+ The active site is then subjected to electron transfer-induced reduction, ultimately forming CO or CH4 products.
7. The use of the Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 6, characterized in that: The Ni-BDC MOF / γ-MnO2 composite photocatalyst material is used in any photocatalytic system to reduce CO2 emissions by converting CO2 into CO and CH4.
8. A method for preparing the Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 1, characterized in that: The following steps are involved: (1) Disperse γ-MnO2 in DMF by ultrasonic method, which is labeled as solution A; (2) Terephthalic acid was dispersed in DMF, labeled as solution B; (3) Ni(NO3)2·6H2O dissolved in deionized water, labeled as solution C; (4) While stirring, add solution A to solution B, and then add solution C dropwise to the mixed solution of solutions A and B, and continue stirring after the addition is completed; (5) The obtained mixed solution is transferred to a hydrothermal reactor and heated for a certain period of time; (6) Filter the precipitate, dry it, and obtain the Ni-BDC MOF / γ-MnO2 composite photocatalyst material.
9. The method for preparing the Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 8, characterized in that: The amount of Ni(NO3)2·6H2O described in step (3) is 7.5 mmol.
10. The method for preparing the Ni-BDC MOF / γ-MnO2 composite photocatalyst material according to claim 8, characterized in that: The mixed solution obtained in step (5) was transferred to a hydrothermal reactor and heated at 180° C. for 24 h.
Citation Information
Cited By
Environment-friendly high-strength impervious cement and preparation method thereof
CN119874289A